490POutcomes of sequential epidermal growth factor receptor tyrosine (EGFR) tyrosine kinase inhibitor (TKI) therapy in patients with advanced non-small cell lung carcinoma (NSCLC)- a real-world institutional experience. (24th November 2019) - Ang, Y; Wong, R; Tan, C S; Blanco, M V; Huang, Y; Goh, B C; Soo, R A
Abstract: Background: EGFR T790M mutations have been reported to occur in about 50% of patients (pts) at progression on 1st/2nd generation EGFR TKI therapy. These pts benefit from treatment with 3rd generation EGFR TKI osimertinib. However, observational real-world studies show that the proportion of pts receiving 2nd line osimertinib is lower than expected. We aimed to evaluate these treatment patterns and outcomes in our institution. Methods: In this prospective observational study, survival, response and treatment data was collected from pts with EGFR mutant advanced NSCLC who received EGFR TKIs in the 1st line, who were treated in our institution from September 2012 to December 2017. Institutional approval was obtained and all patients provided written, informed consent. Results: 108 pts (median age 65 years, 54% females, 75% never smokers, 54% EGFR exon 19 deletion) were enrolled of whom 48 (44%) received gefitinib, 38 (35%) erlotinib and 22 (20%) afatinib in the 1st line. The median overall survival (OS) was 33.1 months (95% CI 24.5-41.7) and median progression free survival (PFS) was 11.1 months (95% CI 8.5-13.7). 83 pts (77%) had progressed at the time of analysis, and 48/83 patients (58%) underwent T790M testing. Of these, 25/48 (52%) were T790M positive. 21/83 pts went on to receive osimertinib in the 2nd line (25% of all patients who progressed on 1st line therapy)- OS was not reached in these pts. 12/83 pts received 2nd line chemotherapy (15%); 32/83 pts (39%) did not receive any 2nd line treatment. OS was 42.3 months (95% CI 24.2-50.4) and 18.2 months (95% CI 11.6-24.7) in these groups respectively. Conclusions: In this prospective real-world study, a significant proportion of patients did not receive 2nd line therapy after progression on 1st/2nd generation TKIs. The rates of T790M mutations when tested was comparable to that reported in the literature. Some reasons for not receiving 2nd line therapy included low testing rates for EGFR T790M and patient fitness for 2nd line therapy. This suboptimal use of osimertinib in the 2nd line setting, together with favourable PFS data for osimertinib in the 1st line, favours the upfront use of osimertinib. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: C.S. Tan: Honoraria (self): AstraZeneca; Honoraria (self): Merck; Honoraria (self): Boehringer Ingelheim; Honoraria (self): Novartis; Honoraria (self): Eli-Lilly; Honoraria (self): Eisai; Honoraria (self): BMS. R.A. Soo: Honoraria (self), Research grant / Funding (self): AstraZeneca; Honoraria (self): BMS; Honoraria (self), Research grant / Funding (self): Boehringer Ingelheim; Honoraria (self): Celgene; Honoraria (self): Ignyta; Honoraria (self): Lilly; Honoraria (self): Merck; Honoraria (self): Novartis; Honoraria (self): Pfizer; Honoraria (self): Roche; Honoraria (self): Taiho; Honoraria (self): Takeda; Honoraria (self): Yuhan. All other authors have declared no conflicts of interest.